Intelligent methods for active noise and vibration control - Tokhi, M. O. (Archives of Acoustics, 2004)
This paper presents an overview of intelligent soft computing techniques within the framework of active control of noise and vibration. Tools considered include genetic algorithms (GAs), neural networks (NNs) and fuzzy logic (FL). The paper highlights associated merits and potential benefits of the approaches in modelling and control of dynamic systems. These are demonstrated in the control of noise in free-field propagation and vibration suppression in 1D and 2D flexible structures. The paper shows that the potential benefits of the individual components can be exploited and approaches for design and development of hybrid soft-computing algorithms devised for modelling and control of dynamic systems. It is demonstrated that significant benefits in terms of performance can be gained with such hybrid algorithms. Keywords: active noise control, active vibration control, fuzzy logic, genetic algorithms, neural networks, modelling of dynamic systems.